Initiation of protein synthesis from a termination codon. - Varshney, U (1990)
We show that the amber termination codon UAG can initiate protein synthesis in Escherichia coli. We mutated the initiation codon AUG of the chloramphenicol acetyltransferase (CAT) gene to UAG (CATam1) and translated mRNA derived from the mutant CAT gene in E. coli S-30 extracts. A full-length CAT polypeptide was synthesized in the presence of tRNA(fMetCUA), a mutant E. coli initiator tRNA which has a change in the anticodon sequence from CAU to CUA. Addition of purified E. coli glutaminyl-tRNA synthetase substantially stimulated synthesis of the CAT polypeptide. Thus, initiation of protein synthesis with UAG and tRNA(fMetCUA) most likely occurs with glutamine and not methionine. The UAG codon also initiates protein synthesis in vivo. To eliminate a weak secondary site of initiation from AUC, the fifth codon, we further mutagenized the CATam1 gene at codons 2 (GAG----GAC) and 5 (AUC----ACC). Transformation of E. coli with the resultant CATam1.2.5 gene yielded transformants that synthesized CAT polypeptide and were resistant to chloramphenicol only when they were also transformed with the mutant tRNA(fMetCUA) gene. Immunoblot analyses and assays for CAT enzyme activity in extracts from transformed cells indicate that initiation from UAG is efficient, 60-70% of that obtained from AUG. Initiation of protein synthesis from UAG using a mutant initiator tRNA allows tightly regulated expression of specific genes. This may be generally useful for overproduction in E. coli and other eubacteria of proteins which are toxic to these cells.